A financial analysis of placing fixed grain assets in northern Kansas - Post, Seth (Kansas State University, 2014)
During the past two decades, there has been major consolidation in the grain handling industry. Staying competitive in today’s environment involves finding projects that add value from a strategic geographic standpoint and a revenue generation standpoint. This study examines several economic factors regarding growth opportunities of facility assets that exist in Northern Kansas, and what the associated cost structure would look like based on a business feasibility study. This study researched the county production by volume and acreage devoted to crop production as well as bid structures and freight spreads of competitors currently in the region today. It also involved researching the margin structures, and it considered a strategic decision about the size of facility that could be built on the existing margin opportunity. Several economic theories were used to derive the feasibility of this research and measure the profitability of the project. Farmer sentiment was polled and a focus group was assembled to understand the opportunity that Scoular may have in the region. The results found a region that provides a steady volume of crop production and margins that are typical of those that Scoular is experiencing in other regions of the state. The research also found the farmers of this geography, receptive to more competition entering the market place.
Keywords: Net present value; Business feasibility; Grain production; Internal rate of return; Agriculture, General (0473); Economics, Finance (0508); Economic Theory (0511)